Agricultural Adaptation to Climate Change: Issues for Developing Countries - Islam , Md. Atiqul (Global Disclosure of Economics and Business, 2013)
One of the burning issues of the world is climate change. The objective of this paper is to review the issues of agricultural adaptation to climate change in the context of developing countries. Literature review type methodology is used here. Total 54 numbers of secondary materials comprising journal articles, books, working papers and documents are used for this research. It is found that Climate Change is real but highly uncertain. It poses threat to agricultural sector of developing countries and adaptation would be a possible solution. Apart from the perception of farmers other factors like the farm family characteristics (e.g. farmers’ education level, farm size, and farm’s financial health) and government support (e.g. access to extension, credit and climate information) could be the potential factors to influence adaptation. There could also be several barriers to adaptation from farmers’ perspective in the face of climate change. Lack of awareness, access to credit, information, knowledge and education to evaluate and implement new methods are the major constraint on adaptation. The appropriate science, actions and policy is required to improve the capacity and to facilitate adaptation in developing countries. JEL Classification Code: Q02; Q18